Post-Marketing Safety Concerns With Secukinumab: A Disproportionality Analysis of the FDA Adverse Event Reporting System - Shu, Yamin; Ding, Yufeng; Liu, Yanxin; Wu, Pan; He, Xucheng; Zhang, Qilin (Frontiers in Pharmacology, 2022)
Purpose: Secukinumab was approved for treatment of psoriasis, psoriatic arthritis and ankylosing spondylitis. However, the long-term safety of secukinumab in large-sample population was unknown. The current study was to evaluate secukinumab-assocaited adverse events (AEs) through data mining of the US Food and Drug Administration Adverse Event Reporting System (FAERS). Methods: Reports in FAERS from the first quarter of 2015 (FDA approval of secukinumab) to the third quarter of 2021 were collected and analyzed. Disproportionality analyses, including the reporting odds ratio (ROR), the proportional reporting ratio (PRR), the Bayesian confidence propagation neural network (BCPNN), and the multi-item gamma Poisson shrinker (MGPS) algorithms, were employed in data mining to quantify the signals of secukinumab-related AEs. Results: A total of 89,228 reports of secukinumab as the “primary suspected (PS)” and 254,886 AEs induced by secukinumab were identified. Secukinumab-induced AEs occurrence targeted 27 system organ classes (SOCs). A total of 257 signals of secukinumab-induced AEs in 19 SOCs were detected after conforming to the four algorithms simultaneously. Common significant signals of infections, respiratory disorders, skin and subcutaneous tissue disorders, immune system disorders, ear and labyrinth disorders have emerged. Unexpected significant AEs such as injection site pain, vessel puncture site haemorrhage, arthralgia, hypokinesia, Bell's palsy, parotid gland enlargement and stress might also occur. The median onset time of secukinumab-associated AEs was 56 days (interquartile range [IQR] 5-214 days), and most of the onsets occurred within the first 1, 2, 3 and 4 months after initiation of secukinumab. Conclusion: Our study found potential new AEs signals and provided a broader understanding of secukinumab's safety profiles, supporting its rational use in chronic systemic inflammatory diseases.